Adaptive content development in PPG learning LMS for Indonesian educational philosophy material based on artificial intelligence and deep learning - Suciptaningsih, Oktaviani Adhi; Khotimah, Khusnul; Mas'ula, Siti; Wijaya, Tommy Tanu; Fauzi, Nasrullah Ali (Jurnal Bidang Pendidikan Dasar, 2026)
The integration of Artificial Intelligence (AI) in higher education offers opportunities for adaptive and personalized learning; however, learning in the Indonesian Educational Philosophy course within the Teacher Professional Education Program (PPG) remains largely monologic, textual, and insufficiently reflective. This study aims to develop AI- and Deep Learning (DL)-based adaptive content integrated into the PPG Learning Management System (LMS). Using a qualitative case study design, the research involved 5 lecturers and 50 pre-service PPG students at Universitas Negeri Malang. Data were collected through observations, interviews, FGDs, documentation, and descriptive questionnaires, and analyzed using Stake’s model (description, interpretation, evaluation). Findings show that AI-integrated adaptive content—through personalized learning paths, NLP-based feedback, and learning analytics—enhances reflective engagement, contextual understanding, and learning effectiveness. The study recommends the development of AI-based LMS ecosystems to support reflective, learner-centered, and contextually meaningful teacher education.